CIAT, CIMMYT, and CIP : their role in agricultural research in Latin America and the Caribbean - Janssen, WG; Crissman, C.C.; Henry, Guy; López Pereira, M.A.; Sanint, Luis Roberto; Walker, T. (International Center for Tropical Agriculture, 1992)
The report discusses how CIMMYT, CIP, and CIAT interact to develop agriculture, particularly in Latin America and the Caribbean (LAC), according to new research trends directed toward environmental conservation and management. Concrete examples are given of achievements so far attained. Five fundamental criteria should be applied in agricultural R&D: relevancy, social productivity, complementarity, flexibility, and profitability. The report confirms the importance of the three IARCs to LAC and their influence on food production indicators, which, during 1966 to 1989, increased for wheat (95.5 percent), rice (93.5 percent), maize (58.2 percent), beans (11.9 percent), potato (56.5 percent), meat (22.5 percent), and milk (34.3 percent). In Bolivia, the area planted to beans increased from 3,000 ha in 1989 to 26,000 ha in 1991. Also discussed are the factors generating changes in the production, food consumption patterns, and marketing of the products researched by CIAT, CIP, and CIMMYT. The impact of these centers on LAC agriculture is examined in terms of development of improved germplasm; institutional development by strengthening research capacities; development of methodologies; networking and information exchange; crop research and management; and postharvest issues. The benefits likely to be produced by research on these basic products by the year 2010 are also estimated. CIAT, CIP, and CIMMYT will explore other dimensions of technology generation related to economic growth with equity, sustainability, and collaborative efforts with the private sector. Research on the production systems of these commodities must continue if these expected benefits are to be obtained.